(untitled) (Patan Pragya, 2024)
This paper presents the numerical solution of Richards Equation of hydrology for unsaturated soils. To describe the prediction and analysis of infiltration - induced landslide due to the heavy and concentrated rainfall, it needs to develop an accurate model for the system. Richards equation of water hydrology may be used to model part of the landslide hazards system in variably saturated (unsaturated) soils. The major problem with the application of Richards’s equation is in the linearization of non-linear partial differential equation. In this work, we apply the empirical relationship developed by Haverkamp et al. to linearize the non-linear PDE. The numerical solution is obtained by using different time stepping schemes and used the outcomes for the calculation of safety factor (FS) prescribed by different infinite slope models. Since safety factor is the index which helps to determine the condition of surface failure situations. From this we can predict the potential landslide area affected by heavy and concentrated rainfall.